HR : the New Agenda. - Norman, Paul. (Knowledge Resources, 2022)
The world has changed irrevocably and a new way of life and work in every aspect is now a reality. This requires HR to review its priorities and place renewed emphasis on being human and building effective human systems and human organisations._x000D__x000D_The old ways of "doing HR" will no longer be relevant and it is time for HR to reimagine itself in a post-Covid world. This new role will demand a "new style" of HR professional, which is what Paul Norman and 17 fellow HR leaders address in HR: The New Agenda._x000D__x000D_The contents include: _x000D_* HR at the Centre_x000D_* The New World of Work_x000D_* The Power of Purpose_x000D_* Changing Perspectives on Employee Health and Wellness_x000D_* Increasing Social Capital_x000D_* Radical New Talent Management Strategies_x000D_* People Development for the New World of Work_x000D_* New IR/ER Dispensation in the Post Covid Workplace_x000D_* Reinventing Remuneration, Benefits and Recognition_x000D_* The New Diversity and Inclusion Realities_x000D_* Governance and Ethics for the 2020s and Beyond_x000D_* Agility and Innovation_x000D_* Developing a Growth Mindset_x000D_* Preparing the HR leader for the Future_x000D__x000D_The Authors include _x000D__x000D_Prof Kurt April; Vanisha Balgobind; Johan Botes; Dr Mark Bussin; Daniela Christos; Wilhelm Crous; Gideon du Plessis; Shelagh Goodwin; Selo Govender; Akona Makoboka; Andrew Millson; Penny Milner Smythe; Jasmin Pillay; Thuli Tabudi; Ninette van Aarde; Dr Dieter Veldsman; Prof Edward Webster_x000D__x000D_Among the companies featured are: Accenture; Discovery; Exxaro; Food Lovers Market; Media24; MTN; Microsoft; Momentum and Spar.